Employability of Higher Education Graduates in the Perspective of Merdeka Belajar Kampus Merdeka (MBKM) - Cahyani, Apreriri; Rugaiyah; Karnati, Neti (Jurnal Manajemen Pendidikan, 2024)
Background Changes in the global order of life also have an impact on higher education transformation in higher education is carried out for universities to adapt to the needs of society and industry. The role of higher education in producing human resources is to produce graduates with a number of abilities that adjust the needs of industry and the world of work in society, which is defined by employability skills. Purpose The writing in this journal reviews how the MBKM curriculum policy is a policy rolled out by the government as an effort to fulfill the employability of higher education graduates. Design/method/approach Through a literature review analyzed from concepts and theories regarding the employability of higher education graduates and the implementation of the MBKM policy. Results The results expected by writing this journal can provide a comprehensive overview of the conditions and role of higher education in producing graduates, supported by government policies that regulate regulations and the need for cooperation between industries in the role of the tri darma of higher education.